An Investigation the Effect of Indicators on Self-Efficacy Using Language toward Indicators of Self-Efficacy Writing Scale - Masrul; Asilestari, Putri (English Education Study Program Faculty of Teacher Training and Education, 2023)
This study investigated the presence of meaningful relationships between the indicators of self-efficacy, including self-efficacy in language, self-efficacy in organization, self-efficacy in grammar, self-efficacy in content, self-efficacy in process and on self efficacy writing scale, including ideation, organization, grammar & spelling, use of English writing, and self-efficacy for self-regulation. Convenience sampling was employed to select 100 students who attended seven different courses at the University of Pahlawan Tuanku Tambusai. The data of this study were analyzed descriptively through data concentration and distribution, pearson correlation, and multiple linear regression. The findings revealed that several self-efficacy indicators namely, SEL, SEO, SEG, SEC, and SEP did not correlate with Ideation (ID), Organization (ORG), Grammar and Spelling (GS), use of English Writing (EW), and Self efficacy for Self Regulation (SR). Keywords: Language Self efficacy, Self efficacy writing scale, Writing in english, Teaching writing